The Metrics of the Physician Brain Drain - Mullan, Fitzhugh (The New England journal of medicine, 2005)
This study found that about a quarter of the physicians working in the United States, the United Kingdom, Canada, and Australia are immigrants who were educated in other countries. Many of these physicians come from lower-income countries, which may cause physician shortages in resource-poor nations. About a quarter of the physicians working in the United States, the United Kingdom, Canada, and Australia are immigrants who were educated in other countries. Many of these physicians come from lower-income countries, which may cause physician shortages in resource-poor nations. The United States, the United Kingdom, Canada, and Australia have been the beneficiaries of large-scale immigration of physicians over the past half century. 1 – 3 Medical-training positions in these developed nations, as well as opportunities for medical employment, have proved a strong draw for physicians from many nations. This medical migration, often called the “brain drain,” has attracted frequent commentary 4 , 5 and has been the subject of deliberations by the Institute of Medicine and the Council on Graduate Medical Education (COGME) in the United States, both of which have expressed concern about heavy reliance on doctors from abroad. 6 , 7 Although some . . .